Dehydrohalogenation reactions in second-sphere coordination complexes. Issue 34 (29th July 2021) - Martí-Rujas, Javier; Guo, Fang
Abstract : An overview on the latest advances in dehydrohalogenation and hydrohalogenation reactions in the solid-state involving hydrogen bonded outer sphere halometallates salts is reported. Abstract : The latest advances of solid-state dehydrohalogenation and halogenation reactions of hydrogen bonded halometallate salts from the second sphere coordination perspective are reported. Since the second sphere englobes many different materials, our focus has been limited to outer sphere adducts where protonated organic cations act as outer sphere hydrogen bond donors and transition metal anions act as first sphere hydrogen bond acceptors. This is our attempt to analyze dehydrohalogenation/hydrohalogenation reactions viewed as transformations from the second sphere coordination to first sphere coordination of a complex and vice versa . The examples describe a unique solid-state chemistry and reactivity in outer sphere adducts where C–H, N–H and M–X chemical bonds are cleaved and new M–N and H–X bonds are formed (where M = Cu, Zn, Co, Pt, Pd, Hg and X = Cl, Br). The transformations are induced by external stimuli, mainly by mechanochemical and thermal methods. Different reactivities have been observed depending on the lability of the transition metals, the position of the reacting functional groups in the cations and the relative position of organic cations and metal anions. The reverse hydrohalogenation reactions ( i.e., from the first sphere coordination to second sphere coordination) via the gas-solid chemisorption process occur even if the materials are non-porous implying a rather dynamic behaviour of these materials. Moreover, due to the implicit changes in the coordination sphere of transition metal ions, dehydrohalogenation/halogenation reactions allow structure – function correlation to be established, for instance involving optical, sensing and magnetic aspects.